2012
DOI: 10.1074/jbc.m112.376590
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-restrictive Silencer Factor (NRSF) Represses Cocaine- and Amphetamine-regulated Transcript (CART) Transcription and Antagonizes cAMP-response Element-binding Protein Signaling through a Dual NRSE Mechanism

Abstract: Background: Cocaine-and amphetamine-regulated transcript (CART) plays a pivotal role in neuroprotection against stroke. Results: Transcriptional repressor neuron-restrictive silencer factor (NRSF) represses CART through binding to two NRSEs in the CART promoter and intron. Conclusion: NRSF represses CART transcription and antagonizes cAMP-response element-binding protein signaling through a dual NRSE mechanism. Significance: This is the first evidence to reveal the repression mechanism of CART transcription. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Similarly, CART-mediated ERK signaling mitigated cortical neuronal demise in response to Aβ toxicity 6 . Further mechanistic examinations have indicated that ischemia-induced suppression of CART expression was modulated by the transcriptional repressor known as neuron-restrictive silencer element 10 . In addition, it has been proposed that attenuation of dopaminergic neuronal cell loss after CART treatment in MPTP-treated mice could be attributed to the anti-oxidative properties of CART 7 .…”
mentioning
confidence: 99%
“…Similarly, CART-mediated ERK signaling mitigated cortical neuronal demise in response to Aβ toxicity 6 . Further mechanistic examinations have indicated that ischemia-induced suppression of CART expression was modulated by the transcriptional repressor known as neuron-restrictive silencer element 10 . In addition, it has been proposed that attenuation of dopaminergic neuronal cell loss after CART treatment in MPTP-treated mice could be attributed to the anti-oxidative properties of CART 7 .…”
mentioning
confidence: 99%
“…Many of the down-regulated DEGs are involved in neurodevelopment by promoting neurite or axon outgrowth, including SEMA3E [53], NTNG1 [54], and CARTPT , which is also involved in stress responses and sensory processing (Fig. 3b) [55]. Additional down-regulated DEGs such as SLIT2 [56] and UNC5D [57] have been shown to function as repulsive neuronal and axon guidance molecules (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent studies revealed that REST induction by ischemia, had more pronounced effects on gene expression, leading to the epigenetic remodeling and suppression of several neuronal genes, which ultimately lead to cell death 53 . Studies using cultured neuroblastoma cell lines, subjected to an in vitro model of ischemia, oxygen and glucose deprivation, also exhibited increased REST mRNA and protein 58 . These studies were the first to identify a potential link between low oxygen and REST regulation ( Table 2).…”
Section: 1-the Repressor Element 1-silencing Transcription Factor (mentioning
confidence: 97%
“…REST is overexpressed in neuronal cancers, and has oncogeneic properties, it inhibits apoptosis and promotes tumorigenisis 74,75 . Interestingly, hypoxic neuroblastoma tumors and cells exposed to hypoxia (1% oxygen) down-regulate neuronal markers 78,79 , and REST protein is induced in oxygen/glucose deprived SK-N-SH neuroblastoma cells 58 . Thus, it is plausible that REST induction by the hypoxic microenvironment known to be present in neuronal tumours 80 , contributes to its oncogenic role.…”
Section: 21-physiological Relevance Of Rest Regulation By Hypoxiamentioning
confidence: 98%